A retrospective (2004-2013) and prospective (2014-2015) audit of surgical diseases of newborn with special reference to gastro-intestinal diseases and emergencies over a period of 10 years at a tertiary care centre - Sharma, Shashishankar; Shukla, Kartikeya; Laddha, Ashok (International Surgery Journal, 2016)
Background:A surgical audit of neonatal surgical diseases especially GIT disorders whereby demanding to establish advanced tertiary neonatal care unit. Methods: A retrospective (2004-2013) and prospective (2014-2015) audit of newborn with surgical diseases especially GIT disorders admitted in a tertiary care center of central India. The trends analyzed for the duration on gender, region and birth weight basis. A data base was generated depicting the burden of diseases in the region. The data base for the prospective study was also compared with a tertiary center from Nigeria. Results:Total 3309 admission included 73.56 % (2438) patients of GIT diseases followed by neural tube defects & hydrocephalus (16.8%), urogenital disorders (3%) and surgical infections. Congenital anomalies were the most common cause in each category, major part being anorectal malformation (727) and trachea-esophageal fistula (730) followed by CNS neural tube defect (431). Out of 3309 admissions, 2392 neonates were operated for different indications of their disorders and total 1194 deaths recorded during this audit year 2004 to July 2014 - July 2015. Majority of new born admitted with were low birth weight male from rural skirts of this region. Conclusions:There is significant increase in admissions in last decade with triple fold increase in GIT disorder and substantially increasing onwards. Demands generated through this audit also encouraged the health officials of this region to provide the paediatric division with two more standard working operation theatres (year 2015) with additional ventilator and resuscitation equipment for SNCU. This development has to continue further to achieve parity with international standards, as there is lack of antenatal screening and details of any antenatal check-up are scarce, for congenital anomalies at primary level. Early recognition, risk stratification of the baby and timely referral to higher paediatric surgery units is the way forward.